2016
DOI: 10.1002/bies.201600065
|View full text |Cite
|
Sign up to set email alerts
|

The light‐driven sodium ion pump: A new player in rhodopsin research

Abstract: Rhodopsins are one of the most studied photoreceptor protein families, and ion-translocating rhodopsins, both pumps and channels, have recently attracted broad attention because of the development of optogenetics. Recently, a new functional class of ion-pumping rhodopsins, an outward Na þ pump, was discovered, and following structural and functional studies enable us to compare three functionally different ion-pumping rhodopsins: outward proton pump, inward Cl À pump, and outward Na þ pump. Here, we review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 85 publications
1
14
0
Order By: Relevance
“…The overall structure of KR2 is very similar to that of microbial rhodopsins in general, such as lightdriven proton and chloride pumps, negative phototaxis and photochromic sensors, and a light-gated channel. 67,68 While the sodium ion was not clearly resolved by the structure of Kato et al, 65 it was observed in the structure of Gushchin et al 66 In the latter structure, KR2 forms pentamers in which the A−C helices are the interaction surface inside each pentamer (Figure 5A). The sodium binding site is located at the boundary of two molecules in the pentamer, where Y25, T83, and F86 of one monomer and D102 of another monomer participate in the binding, as do two internal water molecules (Figure 5A).…”
Section: Structure Of Kr2 a Light-drivenmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall structure of KR2 is very similar to that of microbial rhodopsins in general, such as lightdriven proton and chloride pumps, negative phototaxis and photochromic sensors, and a light-gated channel. 67,68 While the sodium ion was not clearly resolved by the structure of Kato et al, 65 it was observed in the structure of Gushchin et al 66 In the latter structure, KR2 forms pentamers in which the A−C helices are the interaction surface inside each pentamer (Figure 5A). The sodium binding site is located at the boundary of two molecules in the pentamer, where Y25, T83, and F86 of one monomer and D102 of another monomer participate in the binding, as do two internal water molecules (Figure 5A).…”
Section: Structure Of Kr2 a Light-drivenmentioning
confidence: 99%
“…The X-ray structure of KR2 enlightened the location of the ion selectivity filter. A structural comparison between BR and KR2 suggests that relatively bulky residues on the cytoplasmic side of BR (F42, I45, and L224) are replaced by less bulky residues (N61, S64, and G263, respectively) in KR2 (Figure B). This replacement makes the intracellular cavity larger, presumably allowing the entry of a sodium ion into the conducting pathway. Indeed, the shape and size of this pore are major determinants of ion selectivity in KR2, because N61 and G263 mutants are able to pump potassium ions. , Among these mutants, the most efficient potassium pump was N61P/G263W .…”
Section: Structure Of Kr2 a Light-driven Sodium-pumping Rhodopsinmentioning
confidence: 99%
See 1 more Smart Citation
“…Their rhodopsins and their applications have been deeply studied. Besides, several studies have focused on the biotechnological potential of its enzymes [7][8][9][10][11][12][13][14][15]. On the other hand, several culture-independent studies have also shown the presence of members of the genus Natronomonas in different environments from widely separated sites, such as hypersaline and alkaline lakes, solar salterns, saline-alkaline soils, and sediments or oil fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], supporting the widespread distribution of species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished by further integrating light-driven sodium-pumps into the membrane of the vesicle (Fig. 7, R1, lower panel) [134]. Then, the light-driven sodium pumps can operate e.g.…”
Section: B Receiversmentioning
confidence: 99%